Innovations Under a Magnifying Glass of an Economist: What’s New? - S. Huseynov (Цифровое право)
Review of a book Breznitz, D. (2021). Innovation in real places: Strategies for prosperity in an unforgiving world. Oxford University Press. https://doi.org/10.1093/oso/9780197508114.001.0001